Circulating Klotho levels can predict long-term macrovascular outcomes in type 2 diabetic patients. (September 2018) - Pan, Heng-Chih; Chou, Kuei-Mei; Lee, Chin-Chan; Yang, Ning-I; Sun, Chiao-Yin
Abstract: Background and aims: Type 2 diabetes is a global health problem that is associated with a wide variety of vascular complications and associated morbidity and mortality. Klotho is an enzyme and transmembrane protein, and increasing evidence suggests that Klotho may contribute to reduced oxidative stress, improved endothelial function, and vasoprotection. To date, the physiological role of Klotho in vascular complications associated with diabetes is unclear. Methods: We prospectively recruited 252 patients with type 2 diabetes, who visited an outpatient clinic at our hospital between 2009 and 2011. Patients in the top and bottom tertiles of circulating Klotho levels were enrolled for analysis. Results: Of the 168 patients enrolled, 45.8% were male, the mean age was 57.2 years, and the average duration of diabetes was 7.58 years. In multiple regression analysis, a high Klotho level was associated with a reduced risk of developing coronary artery disease and cerebrovascular accidents. Klotho level was also an independent predictor for the development of macroangiopathies within the 7-year study period. Conclusions: Our results suggest that circulating Klotho level is a predictor of long-term macrovascular outcomes in patients with type 2 diabetes. Highlights: The first longitudinal study to suggest the long-term impact of circulating Klotho. First demonstration of a correlation between circulating Klotho and stroke. A high Klotho level predicts a lower risk of coronary artery disease and stroke. Circulating Klotho level is a predictor of macroangiopathies in type 2 diabetes.